Preparation, Identification, and Evaluation of the Thermal Properties of Novolac Resins Modified with TiO2, MgO, and V2O5 Oxides - Mohsen Rezaei Qazviniha; Farideh Piri (Mechanics of Advanced Composite Structures)
It is essential to improve thermal insulation. In this study, titanium dioxide (TiO2), magnesium oxide (MgO), and vanadium pentoxide (V2O5) were used as additives to modify phenolic novolac resin by the solution mixing method. Different weight percentages of resin nanoparticles (NPs) were added, and nanocomposites with different weight percentages were prepared. These nanocomposites were investigated by field emission scanning electron microscope (FE-SEM), X-ray diffraction spectroscopy (XRD), and oxyacetylene flame test (OFT). The FE-SEM images showed that the NPs were dispersed on the surface of the novolac resin at low concentrations. However, at high concentrations, the dispersion was suppressed in some cases by aggregation in the nanocomposites. The OFT test proved that by increasing the content of NPs in the nanocomposite, the back surface temperature of the sample decreased, thus improving the thermal insulation properties.